Dynamic Systems Development Method dalam membangun Aplikasi Data Kependudukan Pada Kelurahan Rantau Pulut - Lili Rusdiana (Jurnal Transformatika, 2018)
Dynamic Systems Development Method (DSDM) can be used as one of the methods in developing and building applications based on the needs and communication of users and developers such as in developing Population Data Application In Rantau Pulut Village. Such as data collection through interviews as one form of communication between developers and users. This research aims to build population applications in Rantau Pulut Village as a solution of data processing both in terms of storage and reporting that can help the processing of data needed to become more effective and efficient as well as a solution for the current system running. Through the stages of DSDM conducted and produce applications that can run in accordance with user needs, especially in terms of reporting generated by the application so that users feel user friendly.